Assistance in Making Natural Hand Sanitizer from Lemongrass Stems and Leaves in Kepuh Village, Palimanan District, Cirebon Regency - Dewiantika Azizah; Indah Karina Yulina; Mutiara Dwi Cahyani; Dewi Nurdiyanti; Banu Kisworo; Tania Avianda Gusman (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
The COVID-19 pandemic left many casualties. The virus attacks the human immune system, which has an impact on physical health, such as: (a) pneumonia, (b) respiratory failure, and (c) death. Hands are one of the parts of the human body that are susceptible to viruses and are the easiest medium for spreading them. Therefore, as a preventive measure to prevent the spread of the virus, hands must always be clean and sterile, which is done by using a hand sanitizer, so that the cleaning process is more effective and efficient. The purpose of this community service activity is to provide awareness to the community to prevent the spread of the virus through the habit of hand sterilization. The target of the service is the residents of the village of Kepuh with the stages of activity, namely preparation, implementation, and evaluation. Preparations were carried out by conducting a preliminary survey to see conditions in the field and obtaining permits for routine mosque activities. Implementation is carried out by cleaning, spraying, and washing mukena. Evaluation of activities is carried out for each stage by collecting and concluding data from each stage of activity. The results of the activity are the washing of mukena, and the cleanliness of the mosque, as well as disinfecting the entire inside and outside of the mosque. The organizers of the activity are lecturers and students and are assisted by the mosque's cleaning staff.